Physical Vapor Deposition Techniques for CO2 Electroreduction: A Review - Samah A. Mahyoub; Arshad Farid; Muhammad Zain Azeem; Danah A. AL Fadhil; Fahim A. Qaraah; Qasem A. Drmosh (Small Structures)
CO2 electroreduction offers a promising approach to reducing the human carbon footprint by converting CO2 into fuels and valuable chemicals. Physical vapor deposition (PVD) techniques, including sputtering, thermal evaporation, and pulsed laser deposition, enable the fabrication of high‐performance catalysts with controlled morphology, strong adhesion, and high purity. These methods allow precise customization of surface features, enhancing catalyst stability and efficiency. PVD facilitates the deposition of various materials, such as metal oxides, alloys, and nanocomposites, making it essential for developing durable catalysts for energy conversion and environmental applications. This review explores the role of PVD in CO2 reduction, focusing on its advantages over alternative deposition techniques like electrodeposition and chemical vapor deposition. It highlights PVD's ability to produce uniform, reproducible films with tailored catalytic properties. Challenges related to scalability, uniformity, and deposition efficiency are discussed, along with potential solutions such as codeposition, multilayer strategies, and hybrid approaches. Future advancements in deposition techniques and material design are also considered to enhance catalyst performance. By addressing these aspects, this review provides insights into optimizing PVD‐based catalysts for efficient and stable CO2 reduction.